Carbon and zeolite-based composites for radionuclide and heavy metal sorption - Darina Smržová; Lórant Szatmáry; Petra Ecorchard; Aneta Machálková; Monika Maříková; Petra Salačová; Martin Straka (Heliyon, 2022)
Zeolites have been investigated as sorbents of heavy metals from water. Since graphene oxide was already reported as promising radionuclide sorbent, we developed composite materials containing both a synthetic zeolite (type A, P or Y) and graphene oxide to be multifunctional sorbents. The extension of multifunctionality of sorbents was done by presence of third component, exfoliated graphite, to have additional properties as conductivity. The changing sorption activities of a composite was studied depending on its composition and functional modification. The composites, characterized by X-ray powder diffraction, Raman, FTIR spectroscopy and scanning electron microscopy, were tested for sorption of selected radionuclides (134Cs+, 85Sr2+) and heavy metals (Pb2+, Cd2+). The dependency on composition was found in connection with a high sorption of Pb2+ and Cd2+. Finally, optimized multifunctional sorbents (Gr-GO-COOH-A in ratio 40:40:20 and Gr:GO:A in ratio 25:25:50) were found to keep interesting high sorption activities for heavy metals and radionuclides with good conductivity properties.